Unveiling botanical blindness between undergraduates and graduates of the Biological Sciences course, Maranhão, Brazil (Research, Society and Development, 2022)
Plant Blindness is characterized by the non-perception of plants in their own environment, making it a problem that makes it difficult to recognize their importance in the biosphere. The objective of this research is to evaluate the influence of Plant Blindness in the formation of Botanical knowledge of undergraduates and graduates of the Biological Sciences course, Maranhão, Brazil. The present work is of the descriptive type with a quantitative-qualitative approach; documental and bibliographical, with consultation in books, articles, master's dissertations, doctoral theses and on official websites. In the research, a questionnaire was applied to undergraduates and graduates in Biological Sciences in the State of Maranhão, through the Google forms platform, containing seven questions, objective and subjective. A total of 105 people were interviewed, all from Higher Education Institutions in Maranhão (IES). Of those interviewed, 51.4% said they did not have Plant Blindness, 40% said yes and 8.6% answered that they might have. The data obtained reveal that Plant Blindness is evident in the graduates and undergraduates of Biological Sciences interviewed, despite the questions showing favorable data for the development of Botany in the courses, much still needs to be improved and a more incisive view of the problem must be carried out.